Da Alta Idade Média à Época Contemporânea: resultados dos trabalhos arqueológicos realizados no Centro Histórico de Oeiras (rua das Alcássimas) entre 2000 e 2007 - Cardoso, João Luís; Cardoso, Guilherme; Batalha, Luísa; André, Maria da Conceição (Estudos Arqueológicos de Oeiras, 2022)
We present the study of post-Roman remains exhumed in excavations carried out between 2000 and 2007 in the Historic Center of Oeiras, in the space previously occupied by a Roman villa famous, for the mosaic found there in 1903 and attributable to the 3rd century AD. The most important conclusion to highlight from this contribution, which follows the publication in 2020 of another archaeological set collected in a nearby location, was the confirmation of the continuous presence communities in that same space until the present day. In fact, remains from the High Middle Ages, the Islamic period, the Christian medieval period, the Modern Period and the Contemporary Period were identified. In this way, the continuity of the urban occupation of the town of Oeiras was demonstrated since the fall of the Roman Empire, a reality now proven through the archaeological works carried out by the Center for Archaeological Studies of the Municipality of Oeiras.